CSR as gendered neocoloniality in the global south - Ozkazanc-Pan, Banu (Journal of Business Ethics, 2019)
Corporate social responsibility (CSR) has generally been recognized as corporate pro-social behavior aimed at remediating social issues external to organizations, while political CSR has acknowledged the political nature of such activity beyond social aims. Despite the growth of this literature, there is still little attention given to gender as the starting point for a con- versation on CSR, ethics, and the Global South. Deploying critical insights from feminist work in postcolonial traditions, I outline how MNCs replicate gendered neocolonialist discourses and perpetuate exploitative material dependences between Global North/South through CSR activities. Specifically, I address issues of neocolonial relations, subaltern agency, and ethics in the context of gendered global division of labor through the exemplar of Rana Plaza and its aftermath. In all, I offer new directions for CSR scholarship by attending to the intersections of gender, ethics, and responsibility as they relate to corporate actions in the Global South.
Keywords: OFDIG; approches et analyses; féminisme décolonial; genre; identités LGBTQIA2+; intersectionnalité; responsabilité sociale des entreprises; ressource en ligne; thématiques; travail